Epistasis, aneuploidy, and functional mutations underlie evolution of resistance to induced microtubule depolymerization. (4th October 2021) - Pavani, Mattia; Bonaiuti, Paolo; Chiroli, Elena; Gross, Fridolin; Natali, Federica; Macaluso, Francesca; Póti, Ádám; Pasqualato, Sebastiano; Farkas, Zoltán; Pompei, Simone; Cosentino Lagomarsino, Marco; Rancati, Giulia; et al.
Abstract: Cells with blocked microtubule polymerization are delayed in mitosis, but eventually manage to proliferate despite substantial chromosome missegregation. While several studies have analyzed the first cell division after microtubule depolymerization, we have asked how cells cope long‐term with microtubule impairment. We allowed 24 clonal populations of yeast cells with beta‐tubulin mutations preventing proper microtubule polymerization, to evolve for ˜150 generations. At the end of the laboratory evolution experiment, cells had regained the ability to form microtubules and were less sensitive to microtubule‐depolymerizing drugs. Whole‐genome sequencing identified recurrently mutated genes, in particular for tubulins and kinesins, as well as pervasive duplication of chromosome VIII. Recreating these mutations and chromosome VIII disomy prior to evolution confirmed that they allow cells to compensate for the original mutation in beta‐tubulin. Most of the identified mutations did not abolish function, but rather restored microtubule functionality. Analysis of the temporal order of resistance development in independent populations repeatedly revealed the same series of events: disomy of chromosome VIII followed by a single additional adaptive mutation in either tubulins or kinesins. Since tubulins are highly conserved among eukaryotes, our results have implications for understanding resistance to microtubule‐targeting drugs widely used in cancer therapy. SYNOPSIS: Cells with blocked microtubule polymerization undergo massive, death‐inducing chromosome missegregation, but may eventually restore microtubule functionality. Here, yeast laboratory evolution shows that this recurrently involves chromosome VIII disomy followed by mutually exclusive mutations in either tubulins or kinesin. After ˜150 generations, budding yeast cells impaired in microtubule formation recover the ability to polymerize tubulin. Genetically‐identical cell populations evolved in parallel exhibit similar evolutionary paths. Evolved cells first become disomic for chromosome VIII, and then acquire mutations in either tubulins or the kinesin KIP3 . Disomy of chromosome VIII is present in the large majority of evolved populations, while mutations are mutually exclusive. Abstract : Laboratory evolution of yeast cells unable to form microtubules shows that their recovery involves a recurring succession of chromosome VIII duplication and adaptive tubulin or kinesis mutations.